Effect of packaging shape and storage on the keeping quality of mineral water and a development of water-treatment device - Abdelsamie, Maher A. A.; Abdul Rahman, Russly; Mustafa, Shuhaimi; Hashim, Dzulkifly (Omics Publishing Group, 2013)
A notable change of quality and increase in the cost of water-treatment devices has resulted from the current watertreatment and packaging techniques in the food industry. Because of these factors, efforts to discover alternative, less stringent packaging techniques have taken a place of high priority in food science. Pyramidal food packages are capable of altering the crystallization mode of water’s mineral content. The effects of pyramidal and square packaging shapes on mineral water were studied by examining ice surface morphology. Ice surface morphology was examined by variable pressure scanning electron microscopy VP-SEM. The pyramid shaped package promotes the formation of filament-shaped crystals, and reduction of solid substrate-bound crystals. These results provide evidence that a pyramidal package acts to structure water and mineral particles in an ordered manner.